Robust Stabilization for Non-linear Applications of Cyber physical Systems - Tahir Anam; Pervaiz Mahmood (Global Science and Technology Forum, 2022)
The stabilization of unstable non-linear compositions is an important and complex phenomenon across the worldwide. The purpose of this research is to model a robust control design for the stabilization of non-linear, unstable, and under actuated applications of Cyber Physical Systems (CPS) using the High Performance Sliding Mode Control (HPSMC) methodology, which has a negligible control errors (chattering) phenomenon. This study focuses on the designing of feedback controllers by means of HPSMC for two applications of CPS i.e., inverted pendulum system and mass spring damper system, both representing non-linear structures. The SMC procedure is based on saturated approximation of the control laws in order to obtain balanced and controlled behavior at, 1) minimum stabilizing time, and 2) unstable equilibrium points while producing negligible chattering occurrences. This technique provides a robust platform for the non-linear, unstable, and under actuated applications of CPS. The systems’ narrations, control objectives, and implementation results of robust feedback controllers are drawn attention to evaluate the reduced control error performance.